2020
DOI: 10.3390/ijerph17103721
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Seniors Hospitalized Due to Cardiovascular Diseases in Poland

Abstract: Introduction: In the light of the increased ageing of the world population, social policy needs to be focused on actions aimed at improving the quality of life of older people. Objective: The main objective of this study was to assess the quality of life in a population of seniors hospitalized due to cardiovascular disease. Materials and methods: The study included 408 elderly patients hospitalized for cardiovascular diseases in the Poddębickie Centrum Zdrowia Hospital in Poddębice, Łódzkie voivodship, Poland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(119 reference statements)
1
1
0
2
Order By: Relevance
“…We also found that the age group of >73 reported lower QoL because of physical and emotional limitations that were reported compared to other age groups, such as 66-72 years old. This is an expected outcome that is also confirmed by the findings of other studies which showed that QoL is severely affected to the elderly population [ 9 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…We also found that the age group of >73 reported lower QoL because of physical and emotional limitations that were reported compared to other age groups, such as 66-72 years old. This is an expected outcome that is also confirmed by the findings of other studies which showed that QoL is severely affected to the elderly population [ 9 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the mean scores for MCS and PCS of HRQOL were 63.6 (7.8) and 67.8 (10.8) out of 100 points, respectively. The mean scores of HRQOL within our sample were considerably higher than the mean scores of MCS and PCS of elderly patients hospitalized for cardiovascular disease [ 40 ] and long-term dialysis patients [ 41 ]. This finding suggested that with the progression of the chronic diseases, health intervention should include different chronic disease programs to manage chronic conditions and strengthen health status.…”
Section: Discussionmentioning
confidence: 88%
“…K rozdílným výsledkům dospěla také studie z Polska, kde byla zjištěna statisticky významná korelace mezi pohlavím a doménou fyzické zdraví a rovněž mezi pohlavím a celkovým skóre fyzické složky kvality života -muži v těchto doménách udávali lepší kvalitu života. 18 Tato variabilita výsledků může být podle našeho názoru způsobena odlišnými sociodemografi ckými poměry v jednotlivých zemích a také volbou jiného nástroje pro hodnocení kvality života. Přesto, že některé nástroje použité v polské i řecké studii lze použít také pro starší populaci, nepokrývají tyto dotazníky na rozdíl od námi použitého nástroje žádné oblasti, které jsou pro seniory výlučně důležité.…”
Section: Diskuseunclassified